1997
DOI: 10.1063/1.120163
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of (00.1) GaN epilayers grown on a (00.1) sapphire

Abstract: The polarity is found to be a key parameter for the growth of high quality epitaxial GaN films on sapphire (00.1) substrates. A model is suggested which may consistently explain the observed influence of the process parameters on the polar orientation of the epitaxial film. A simple etching technique is proposed for quick distinction of the film polarity. The assignment of the etching behavior to the proper crystal structure is achieved by an analysis of the respective two-dimensional photoelectron diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(116 citation statements)
references
References 10 publications
7
106
2
Order By: Relevance
“…The ͑0001͒ Ga-terminated surface was exposed to solution. 9 A standard three electrode cell was used for the electrochemical experiments. All potentials are reported with respect to the standard calomel electrode.…”
mentioning
confidence: 99%
“…The ͑0001͒ Ga-terminated surface was exposed to solution. 9 A standard three electrode cell was used for the electrochemical experiments. All potentials are reported with respect to the standard calomel electrode.…”
mentioning
confidence: 99%
“…This first step is required because the c-plane {0001} is impervious to all chemical agents investigated, 12,13 except at defect sites where etch pits occur. 14,15 In the second step the semiconductor sample is immersed in a hot chemical etchant that is able to crystallographically etch GaN.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed study of the surface morphology of the GaN films with the different polarities [15] has revealed that the Ga-face (0001) surface is much smoother than the surface with N-polarity (000 1 ). Therefore, films with Ga-polarity are preferable for applications.…”
Section: Disscusionmentioning
confidence: 99%